Preventing NSAID-induced Gastropathy: The Role of Mucus Cells to Prevent Aspirin-Induced Acute Gastric Mucosal Damage - Chudahman Manan; Bambang Pontjo Priosoeryanto; Daldiyono Daldiyono; Sri Estuningsih; Min Rahminiwati (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Mucus is pre-epithelial gastric layer that may prevent damages due to direct contact between aspirin and gastric epithelial cells. The integrity of gastric mucosa and mucous cellular reaction may serve as primary and secondary prevention of extended aspirin-induced gastric mucosal damage. The aim of this study was to prove the function of mucus as defensive factor in rats. Method: The study was conducted in twenty white rats of the Sprague-Dawley strain at Department of Pathology and Clinical Reproduction, Bogor Agricultural University, between January and December 2008. The rat in the treatment group were given 400 mg aspirin diluted in aqua bidest through intra- gatric canules; while the control group received aqua bidest only once daily for 3 days. Necropsies, macroscopic and microscopic observation were performed by counting the number of Alcian blue- periodic acid Schiff-stained mucous cells at fundus/corpus and antrum/pylorus regions. Data analysis was performed using ANOVA and Duncan test. Results: The number of mucous cells with positive lesions in the treatment group was significantly different from the control group at both regions. There was no significant difference of negative lesions between treatment and control group at both regions. At antrum/pylorus region, there was no difference of negative lesions between treatment and control groups; however, both groups demonstrated significant difference of positive lesions in treatment group. Conclusion: In primary prevention for gastric mucosal lesions, there is no increasing number of mucous cells in normal mucosa. Increasing number of mucous cells is a secondary prevention against extended aspirin-induced gastric mucosal damage. Keywords: NSAIDs/ASA, mucus cells, gastric mucosal lesion, rat